2012
DOI: 10.1111/ahe.12004
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Structure and Oogenesis of Catfish Pimelodella vittata (Lütken, 1874) (Siluriformes, Heptapteridae)

Abstract: The morphology of the ovaries and oogenesis of Pimelodella vittata were studied using anatomical and histological techniques to provide information of its reproductive biology. Eighty adult females were captured trimonthly during the period November 2005 to October 2006. The ovaries are paired, saculiform organs, which are coated with tunica albuginea and contain ovigerous lamellae, where the oocytes develop before being released into the ovarian lumen and following the ovarian duct until reaching the genital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The oogenesis was similar to that observed in other Siluriformes with external fertilization (Melo et al 2011, Sales et al 2012, as well as, the histochemistry analysis of oocyte structures (Bazzoli and Godinho 1994). In H. francisci, during the development of oocytes, the zona radiata became visible in pre-vitellogenic oocytes and PAS-positive, indicating neutral glycoproteins.…”
Section: Discussionsupporting
confidence: 82%
“…The oogenesis was similar to that observed in other Siluriformes with external fertilization (Melo et al 2011, Sales et al 2012, as well as, the histochemistry analysis of oocyte structures (Bazzoli and Godinho 1994). In H. francisci, during the development of oocytes, the zona radiata became visible in pre-vitellogenic oocytes and PAS-positive, indicating neutral glycoproteins.…”
Section: Discussionsupporting
confidence: 82%
“…Most Siluriformes present a pair of lobulated fringed testes, some of these showing a conspicuous seminal vesicle (Parreira et al., ) and others with a secretory caudal region (Santos et al., ). The ovaries are also paired and of the ovarian cyst type, with complete capsule and duct communicating with genital papilla (Sales et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Gallo and Constantini (2012) suggest that the GC pattern is specific to the species. In this work we have observed that the G. blacodes cortical alveoli possess neutral GCs just as other teleosts, like Lophiosilurus alexandri (Barros et al, 2007), Heterandria formosa (Uribe and Grier, 2011) and Pimelodella vittata (Sales et al, 2013). Through lectin histochemistry it was possible to detect a great variety of sugar residues in the cortical alveoli that reacted positively with most of the employed lectins.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, the zona radiata is responsible for the interaction of eggs in water and the protection of the embryo against microorganisms (Sales et al, 2013). Riehl and Patzner (1998) describe the teleosts zona radiata usually consisting of a proteic inner layer and an outer layer that mainly contains neutral and acid GCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation